The End of Landscape in Nineteenth-Century America - Cao, Maggie M., 1983- (Book collections on Project MUSE., 2018)
"The End of Landscape in Nineteenth-Century America examines the dissolution of landscape painting in the late nineteenth-century United States. Focusing on the unorthodox artworks of four painters--Albert Bierstadt, Martin Johnson Heade, Ralph Blakelock, and Abbott Thayer--Maggie M. Cao proposes a new way of thinking about these artists' unexpected interventions and how they challenged, mourned, or revised the conventions of landscape painting, a major cultural project for nineteenth-century Americans. Through rich analysis of artworks at the genre's unsettling limits, Cao shows that landscape played a crucial role in the American encounter with modernity and was the genre through which American art most urgently sought to come to terms with the modern world"--Provided by publisher